Supervening impossibility of provision in times of pandemic - Cortez de Carvalho, Priscila (Seven Editora, 2023)
The present study aims at the doctrinal survey of the situations in which the theory of supervening impossibility of provision was invoked considering the global pandemic scenario by COVID-19. To this end, we seek to differentiate the proposed theses to address the situations in which the provision suffered an unpredictable obstacle due to the mandatory social distancing, with the limitation of several activities, causing a considerable crisis in contractual relations. DOI: 10.56238/pacfdnsv1-045